Reduced ex vivo susceptibility of Plasmodium falciparum after oral artemether–lumefantrine treatment in Mali. (December 2017) - Dama, Souleymane; Niangaly, Hamidou; Ouattara, Amed; Sagara, Issaka; Sissoko, Sekou; Traore, Oumar; Bamadio, Amadou; Dara, Niawanlou; Djimde, Moussa; Alhousseini, Mohamed; Goita, Siaka; Maiga, Hamma; et al.
Abstract Background Artemisinin-based combination therapy is the recommended first-line treatment for uncomplicated falciparum malaria worldwide. However, recent studies conducted in Mali showed an increased frequency of recurrent parasitaemia following artemether–lumefantrine (AL) treatment. Methods Study samples were collected during a large WANECAM study. Ex-vivoPlasmodium falciparum sensitivity to artemether and lumefantrine was assessed using the tritiated hypoxanthine-based assay. The prevalence of molecular markers of anti-malarial drug resistance (pfcrt K76T, pfmdr1 N86Y and K13-propeller) were measured by PCR and/or sequencing. Results Overall 61 samples were successfully analysed in ex vivo studies. Mean IC50 s increased significantly between baseline and recurrent parasites for both artemether (1.6 nM vs 3.2 nM, p < 0.001) and lumefantrine (1.4 nM vs 3.4 nM, p = 0.004). Wild typePfmdr1 N86 allele was selected after treatment (71 vs 91%, 112 of 158 vs 95 of 105, p < 0.001) but not the wild typepfcrt K76 variant (23.5 vs 24.8%, 40 of 170 vs 26 of 105, p = 0.9). Three non-synonymous K13-propeller SNPs (A522C, A578S, and G638R) were found with allele frequencies <2%. Conclusion Malian post-ALP. falciparum isolates were less susceptible to artemether and lumefantrine than baseline isolates.